Forests in Digital Games - An Ecocritical Framework - Thibault Mattia; Galeote Daniel Fernández; Macey Joseph; Jylhä Henrietta (United States, 2025)
Forests are, both culturally and ecologically, one of the most important environments on our planet. As such, there are countless representations of them - with Digital Games being no exception. In this paper we adopt the perspective of ecocriticism, which regards the analysis of the textual portrayal of physical environments of the natural world. In particular, we propose here a framework for the analysis of forest representations in digital games, mindful of the many different layers that coexist together: cultural, discursive, representational and ludic. In order to test our framework and to showcase its potential, in the last section we present a brief analysis of the slicing game Jack Lumber and of the ideological tensions that emerge from the game.
FDG '22: Proceedings of the 17th International Conference on the Foundations of Digital Games